Effects of Ginger (Zingiber officinale) Supplementation via Drinking Water on Growth Performance and Intake Responses of Heat-Stressed Broilers - Marquez-Cadoy, Jessica; Nicolas, Karina Marie (International Journal of Sustainability and Advanced Integrated Research, 2026)
Heat stress is a major constraint in poultry production, particularly in tropical environments, adversely affecting growth performance, feed efficiency, and overall physiological function. This study evaluated the effects of powdered ginger (Zingiber officinale) supplementation via drinking water on growth performance, feed intake, feed conversion ratio (FCR), and water intake of broiler chickens under heat stress, following phytochemical characterization of the ginger powder. A total of 150 Cobb 500 broilers were randomly assigned to five treatments: control (plain water), 1.5 g/L, 2.5 g/L, 3.5 g/L, and 4.5 g/L ginger supplementation in drinking water. Birds were exposed to cyclic heat stress (32– 35 °C for 6 h daily) from day 15 to 35. Phytochemical analysis of the ginger powder revealed the presence of phenolics (8.86–10.19 mg GAE/g), flavonoids (4.16–4.55 mg CE/g), tannins (0.41–0.45 mg CE/g), and measurable antioxidant activity (29.61–31.45% DPPH scavenging), indicating its potential as a functional phytogenic additive. Ginger supplementation did not significantly affect (P > 0.05) body weight, weight gain, feed intake, FCR, or water intake across most weeks. Ginger supplementation did not significantly affect (P > 0.05) overall growth performance, feed intake, FCR, or water intake. However, treatment-specific responses were observed. Broilers in the 4.5 g/L group (T5) consistently showed the highest final body weight (2122.22 g) and cumulative weight gain (2082.22 g), along with the highest cumulative feed intake. The 3.5 g/L group (T4) recorded the lowest numerical FCR (1.58) and the highest weight gain during Week 4 (P < 0.05), indicating improved feed utilization during peak heat stress. Meanwhile, the 2.5 g/L group (T3) demonstrated stable growth performance across the experimental period. Water intake increased with heat exposure but was not affected by ginger supplementation, indicating good palatability. Overall, ginger supplementation supported performance stability under heat stress, with 4.5 g/L enhancing growth, 3.5 g/L improving feed efficiency, and 2.5 g/L providing consistent performance.